Analysis of Poisoning Cases at a Tertiary Care Hospital in Bahawalpur - Tehreem Abaid, Hira Anjum, Talha Naeem Cheema, Ahmad Raza Khurram, Aftab Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The objective was to analyse the poisoning cases coming at A&E Department B.V Hospital Bahawalpur with regard to demographic profile and fatality. Study Design: Cross Sectional Study (Descriptive) Setting and Duration of Study: This study was carried out at A&E Department B.V Hospital Bahawalpur, covering a span of one year. i.e 1st January 2017 to 31st December 2017. Materials and Methods: A total of 2261 cases were included in this study. After, history was taken, perusal of treatment notes was done, performa was filled and the demographic profile with type of poison was noted. Results: Out of 2261 cases, 1625 (72%) were male and 636 (28%) were females. Most common age group affected was 21-40 years n=1080(48%), while least number of cases noted in above 60 years of age n=95(4%). Maximum number of Black Stone (PPD) n=1093 (48.4%) cases were examined while wheat pills poisoning was recognised as highest toxic agent (45% mortality). Conclusion: In conclusion, our study shows predominant ages were between 21-40 years and males accounted for maximum number of cases. Suicidal intention was commonest manner and PPD was the most frequent one. Wheat pills surfaced as the most lethal poison. Keywords: Poisoning, Paraphenylene Diamine (PPD), Aluminium Phosphide (Wheat pills). Drugs of Addiction